2023
DOI: 10.1002/smll.202207131
|View full text |Cite
|
Sign up to set email alerts
|

Cleanroom‐Free Fabrication of Microneedles for Multimodal Drug Delivery

Abstract: Microneedles have recently emerged as a powerful tool for minimally invasive drug delivery and body fluid sampling. To date, high‐resolution fabrication of microneedle arrays (MNAs) is mostly achieved by the utilization of sophisticated facilities and expertise. Particularly, hollow microneedles have usually been manufactured in cleanrooms out of silicon, resin, or metallic materials. Such strategies do not support the fabrication of microneedles from biocompatible/biodegradable materials and limit the capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…However, as these commercial resins were not originally formulated with biodegradability in mind, their functionality within biomedical applications may be limited. A number of studies have been conducted on formulation of biocompatible polymers for VP fabrication [ 34 , 82 , 83 ], allowing for the possibility to incorporate different properties into the printed parts.…”
Section: D-printed Mnsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as these commercial resins were not originally formulated with biodegradability in mind, their functionality within biomedical applications may be limited. A number of studies have been conducted on formulation of biocompatible polymers for VP fabrication [ 34 , 82 , 83 ], allowing for the possibility to incorporate different properties into the printed parts.…”
Section: D-printed Mnsmentioning
confidence: 99%
“…This method involves printing a MN master template, which is used to make a negative mold. Hydrogel formulations are then casted into the negative mold to obtain dehydrated or shrunken MNs of the desired shape and size [ 83 , 101 ]. While preservation of the original structure and geometry during shrinking is a concern, Wang et al has showed that by attaching the base of the hydrogel MN to a polycarbonate film, uniform shrinking of the MN patch is achieved [ 101 ].…”
Section: D-printed Mnsmentioning
confidence: 99%
See 1 more Smart Citation
“…124 3D printing has the advantages of high resolution printing, high printing speed and low printing cost, and it has become the preferred process for preparing hollow microneedles and microneedles with complex structures. Ghanbariamin et al 125 used low-cost 3D printing technology to prepare PEGDA/GelMA hydrogel microneedles with large sizes and then repeatedly contracted the hydrogel microneedles to prepare solid and hollow microneedles with controllable sizes.…”
Section: Microneedlementioning
confidence: 99%
“…The disadvantage is that it is too brittle to break easily like silicon. 42 According to the characteristics of different processing behaviors, there are thermoplastic and thermosetting resins. Commonly used are polyvinylpyrrolidone (PVP), polycarbonate (PC), epoxy resin and so on, among which PVP is a thermoplastic resin polymerized from ethylene.…”
Section: Characteristics Of the Mn Partmentioning
confidence: 99%